Financial Planning and Evaluation for the Nonprofit Organization (Book). - Meyer, Philip E.; Freeman, Robert J. (The Accounting Review, 1982)
Abstract Reviews the book "Financial Planning and Evaluation for the Nonprofit Organization," by Anthony J. Gambino and Thomas J. Reardon.